An analysis of idiomatic expressions used in “The Call of the Wild” movie - Erika Vonny Cornelia; A. B. Prabowo Kusumo Adi; Maria Yosephin Widarti Lestari (Universitas Aki, 2023)
Analysis of Idiomatic Expressions in the Movie